2012
DOI: 10.1159/000337182
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Induces Rapid eNOS Phosphorylation and Vasodilation by an Akt-Independent and PKA-Dependent Mechanism

Abstract: Consumption of the flavonoid quercetin exerts beneficial effects on many chronic diseases. The mechanisms involved in the vasorelaxant effect of quercetin remain uncertain. In the present study, we examined the role of quercetin in vasodilation and rapid endothelial nitric oxide synthase (eNOS) activity in endothelial cells. Quercetin induced a rapid, dose-dependent phosphorylation of eNOS at serine 1179. PKA, Akt and ERK1/2 were all quickly phosphorylated in the process too, but not AMPK and CaMK II. The spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 50 publications
1
38
1
Order By: Relevance
“…Consistent with our observation, many researchers have shown that quercetin glucosides activate endothelial nitric oxide and improve endothelial function (Li et al, 2012;Sanchez et al, 2006;Shen et al, 2012). Murohara et al reported that impaired angiogenesis in eNOS−/− mice was not improved by administration of vascular endothelial growth factor (VEGF), suggesting that eNOS acts downstream from VEGF (Murohara et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our observation, many researchers have shown that quercetin glucosides activate endothelial nitric oxide and improve endothelial function (Li et al, 2012;Sanchez et al, 2006;Shen et al, 2012). Murohara et al reported that impaired angiogenesis in eNOS−/− mice was not improved by administration of vascular endothelial growth factor (VEGF), suggesting that eNOS acts downstream from VEGF (Murohara et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that both eNOS and nNOS (neuronal nitric oxide synthase) could play intrinsic roles in the process of arterial baroreception [27,28]. However, our experiments show that CMT has no effect on nNOS activity in the carotid bifurcation tissue.…”
Section: Discussioncontrasting
confidence: 72%
“…cAMP is a central signaling molecule in a variety of cellular systems. PKA is generally cAMP dependent, and cAMP stimulates eNOS phosphorylation by PKA-dependent mechanisms [27][28][29], suggesting that cAMP is upstream of PKA-mediated eNOS activation. Our results indicate that CMT induced a dosedependent increase in intracellular cAMP and phosphorylation of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, quercetin-mediated antiplatelet activity involves PI3K/Akt inactivation, cAMP elevation, and VASP stimulation that, in turn, suppresses MAPK phosphorylations [98]. Intraplatelet cAMP production was quickly increased by quercetin stimulation and probably through the adenylate cyclase signaling pathway [130]. …”
Section: Mechanism Of Antiplatelet Action Of Natural Productsmentioning
confidence: 99%